Management of the pharmacological treatment in patients with chronic obstructive pulmonary disease - Bastos, Celeste (2019)
Background: Chronic obstructive pulmonary disease (COPD) is a chronic and incapacitating disease, whose regimen includes inhalation medication. The evidence shows a low adherence, which may increase the aggravation of the disease. Objectives: To study the adherence and the perceived competence of patients to comply with the treatment regimen of COPD and evaluate their knowledge on the use of inhalers. Methodology: Quantitative and cross-sectional study, participants were 45 patients with COPD. We used the Medication Adherence Rating Scale (MARS), the Perceived Competence Scale (PCS), and a questionnaire on the use of inhalers. Results: Participants reported good adherence to the medication regimen and reported a high degree of perceived competence to maintain the treatment regimen of COPD. However, they manifested little knowledge about the use of inhalers and the inhalation technique, which compromises the effectiveness of the established therapeutic plans and exacerbate the deterioration of the clinical condition. Conclusion: This study suggests that nursing care should be developed with a focus on knowledge and training in the inhalation technique.